Tradycja i kultura Indii w dokumencie filmowym Andrzeja Fidyka Kiniarze z Kalkuty - Fiołek-Lubczyńska, Bogumiła (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2013)
Andrzej Fidyk is a documentary director. He documents reality using devices familiar to a typical director. He goes around the world, showcasing the unknown, and other cultures and traditions for his viewers. “Calcutta’s Moviegoers” is a film about India’s love for its native cinema. Fidyk shows the culture of India, and the rituals of the country by observing Indians, their behaviour, and their approach to tradition. In his research, he is an “anthropologist” with a camera.